PERAN KOPERASI SYARIAH DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI DI KOTA JAYAPURA - LUTDIN WABULA (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2025)
Sharia cooperatives hold strategic potential in improving the economic welfare of communities, particularly in regions facing geographical challenges and limited infrastructure such as Papua. This study aims to analyze the role of sharia cooperatives in empowering members’ economies in Jayapura Regency and Sentani District. A descriptive qualitative method was employed, with data collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that sharia cooperatives significantly contribute to increasing members’ income by 10–30% and enhancing business skills through management, marketing, and continuous mentoring programs. Furthermore, they reduce members’ dependence on high-interest financing, encourage product innovation based on local resources, and strengthen social solidarity. Despite challenges such as limited marketing networks, low product diversification, and minimal digital literacy, sharia cooperatives remain effective instruments for value-based and culturally integrated economic empowerment. This study recommends strengthening marketing partnerships, utilizing digital technology, and diversifying products as sustainable strategies for the cooperatives’ development.